Sleep and motor sequence learning consolidation in former iron deficient anemic adolescents - Reyes, Sussanne; Algarín, Cecilia; Lozoff, Betsy; Peigneux, Philippe; Peirano, Patricio (Sleep medicine, 2019)
Iron deficiency is the most prevalent micronutrient deficiency worldwide. There is evidence that iron deficiency produces alterations in the developing brain, eventually leading to long-lasting effects on various cognitive functions. Here, we investigated motor learning and its consolidation after sleep in adolescents who sustained iron deficiency anemia (IDA) in infancy, compared to healthy controls, in the context of a long-term follow-up Chilean research project. Fifty-three adolescents who formerly had iron deficiency anemia as infants and 40 control adolescents practiced a sequential motor finger tapping task, before and after a night of sleep. Performance was measured at the end of learning, 30 min later (boost effect), and the next morning. Revealed slower learning in subjects with infant iron deficiency anemia than control subjects, followed by a proportionally similar performance boost at 30 min. Performance remained stable overnight in healthy controls but further improved in infant IDA adolescents, suggesting a beneficial effect of post-training sleep on the consolidation of incompletely learned motor skills. In particular, overnight gains in performance were observed in female, but not male infant iron deficiency anemic subjects, suggesting a gender effect. Our results indicate long-lasting motor learning deficits in infant IDA adolescents and provide support to the hypothesis that post-training sleep might, to some extent, compensate for hampered motor learning during wakefulness. •Iron deficiency anemia in infancy affects motor skills learning in adolescence.•Sleep can further improve motor learning performance in formerly iron deficient anemic (FIDA) adolescents.•Female FIDA adolescents who have the lowest performance are those who benefit from sleep.